Clinical aspects of mucosal healing in inflammatory bowel diseases: what is it and what is the real value for the everyday practice?. (September 2013) - Miheller, Pal; Mandel, Michael D; Mullner, Katalin; Lakatos, Peter L
The course of inflammatory bowel diseases is heterogeneous and varies over time. Therefore, the search for predictive factors has increasingly become the focus of research. Mucosal healing has emerged as an important objective, as evidence indicates that it is associated with improved disease outcome. Nevertheless, many unsolved questions remain, including the definition of complete or partial healing as well as the best assessment method using endoscopic or imaging techniques, most of which are relatively invasive and expensive procedures, which therefore are not ideal for frequent monitoring and it is not clear. This review summarizes the available evidence in order to assist clinicians when assessing the mucosal status in the everyday practice.